(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
During the 18th century, five Franciscan missions were established in the current metropolitan area of San Antonio, Texas. These communities contributed to the conversion of native people, favoring the local strengthening of the Spanish authority. However, French and Indian raids led to the construction of defensive systems. The missions, therefore, became fortified settlements, protecting one of main crossroads of the New World. Such typological innovation was supported by the Papal Congregation of Propaganda Fide. The layout was wisely developed, adopting Spanish and Italian Renaissance treatises’ principles and models. Regular geometries and specific construction features characterized the design of walled enclosures, similar to the ones of the nearby Spanish presidios. In San Antonio missions, military architecture is intertwined with Christian symbolism in an emblematic syncretism between European traditions and local peculiarities. Once secularized, these settlements became rural communities, with the exception of Mission San Antonio, which was converted in the Alamo fort. The missions were rediscovered at the beginning of the 20th century, and pivotal for the entire nation are their first conservation efforts starting from the 1920s. Keywords: Missioni di San Antonio (Texas), architettura, Settecento, restauro, Novecento.